ANALISIS GAYA KEPEMIMPINAN KEPALA DESA DALAM MENGATASI KONFLIK DI DESA MERTAK TOMBOK DAN DESA BUNUT BAOQ KECAMATAN PRAYA KABUPATEN LOMBOK TENGAH - ROSSI MAUNOFA WIDAYAT; L. SOPAN TIRTA KUSUMA; DARMANSYAH . (Universitas Mahasaraswati Mataram, 2018)
This research reveals the phenomenon of village autonomy, which currently with the Law No. 6/2014 has made the village as the center of attention of all parties. Within the scope of village leadership, the leadership style of the village head can be used as a benchmark against the direction of village objectives. As is the case in Central Lombok District, from 2011-2013 the increasing conflict every year occurs in political conflicts, conflicts of economic resources, custom conflicts, fights between villages, and persecution. This research is a descriptive research which aims to find out the model of leadership style used by the Village Head Mertak Tombok and Bunut Baoq Village and the role and influence of the leadership style model used to prevent complication and conducive of Mertak Tombok Village and Bunut Baoq Village. Data is collected through field research, using informant purposively sampling. The data that have been collected are analyzed qualitatively, ie data from the interviews obtained, then analyzed descriptive by using narrations or words The results shows that 1). Head of Mertak Tombok Village has a transformational leadership style, while for Bunut Village Baoq has Paternalisitic leadership style, 2). The leadership style that each village leader possesses and the awiq-awiq of the village participate in and influence in preventing the conflict and the conduciveness of the village. For Mertak Village Tombok has awig-awig ban of visiting time past 22.00 WITA, while Bunut Baoq Village has awiq-awiq ban to present Kecimol (Typical Arts of Sasak tribe) in the Village